2021
DOI: 10.3389/fonc.2021.723888
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Potential of T Memory Stem Cells

Abstract: Memory T cells include T memory stem cells (TSCM) and central memory T cells (TCM). Compared with effector memory T cells (TEM) and effector T cells (TEFF), they have better durability and anti-tumor immunity. Recent studies have shown that although TSCM has excellent self-renewal ability and versatility, if it is often exposed to antigens and inflammatory signals, TSCM will behave as a variety of inhibitory receptors such as PD-1, TIM-3 and LAG-3 expression, and metabolic changes from oxidative phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 165 publications
(195 reference statements)
1
31
0
Order By: Relevance
“…Additionally, T SCM is the precursor of memory cells and presents naïve‐like biomarkers (CCR7, CD27, CD127 and CD62L). T SCM has enhanced self‐renewal and proliferation capabilities, and has a multipotent developmental potential to generate multiple subsets of memory cells 18, 19 . The memory T cell mentioned in this article mainly refers to T CM .…”
Section: The Variable Metabolic Demands Throughout T Cell Differentia...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, T SCM is the precursor of memory cells and presents naïve‐like biomarkers (CCR7, CD27, CD127 and CD62L). T SCM has enhanced self‐renewal and proliferation capabilities, and has a multipotent developmental potential to generate multiple subsets of memory cells 18, 19 . The memory T cell mentioned in this article mainly refers to T CM .…”
Section: The Variable Metabolic Demands Throughout T Cell Differentia...mentioning
confidence: 99%
“…T SCM has enhanced self-renewal and proliferation capabilities, and has a multipotent developmental potential to generate multiple subsets of memory cells. 18,19 The memory T cell mentioned in this article mainly refers to T CM .…”
Section: The Variable Metabolic Demands Throughout T Cell Differentia...mentioning
confidence: 99%
“…The T SCM subset has been identified in mice ( 15 ), non-human primates ( 16 , 17 ), and humans ( 18 , 19 ). In humans, approximately 2-4% of peripheral blood T cells consist of T SCM cells ( 20 ). The T SCM cells are phenotypically defined as naïve T (T N ) cells by the expression of T N cell markers, such as CD45RA, CD62L and CCR7, but are distinguishable from T N cells by two memory T cell markers: CD95 and CD122.…”
Section: Introductionmentioning
confidence: 99%
“…We designed a combined panel of surface memory/exhaustion markers such as CD62L, CD45RO, CCR7, and PD-1 and the transcription factor TCF1. We observed that the culture conditions favored the expression of cells with a central memory phenotype (Tcm and CD62L+/CD45RO+), which are the best candidates for a sustained in vivo response ( 52 ). In addition, the cells that expanded with our culturing conditions sustained the expression of TCF1 and CCR7, thereby facilitating the maintenance of a stem cell-like state.…”
Section: Discussionmentioning
confidence: 99%